MATHEMATICAL MODELING OF THE MAXIMUM LENGHT OF HYDRAULIC CHANNEL IN A NATURAL WATERCOURSE VIA COMPUTERS - G. A. Alibekov (Вестник Дагестанского государственного технического университета: Технические науки)
The present paper is devoted to finding the maximum possible length of hydraulic passages extending in a natural line for the given parameters of useful effect coefficient and other performance parameters of polygonal section of the channel, using a set of computer programs.